2012
DOI: 10.1007/s10815-012-9755-5
|View full text |Cite
|
Sign up to set email alerts
|

Importance of sperm gluthatione treatment in ART

Abstract: Our results show that sperm PCC formation could be one of the major causes of failed fertilization in individuals with sperm abnormalities. Also sperm PCC formation may be involved in the etiology of some cases of idiopathic infertility. Given that the susceptibility of sperm to oxidative stress is significantly greater in idiopathic infertile men, our results show that treatment with glutathione could significantly reduce these stress factors and increase ART outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…60 Recently, Meybodi et al demonstrated in an animal study that glutathione treatment might increase ART outcomes. 61 They found that glutathionetreated spermatozoa exhibited higher oocyte penetration rates.…”
Section: Glutathionementioning
confidence: 99%
“…60 Recently, Meybodi et al demonstrated in an animal study that glutathione treatment might increase ART outcomes. 61 They found that glutathionetreated spermatozoa exhibited higher oocyte penetration rates.…”
Section: Glutathionementioning
confidence: 99%
“…Asthenozoospermic sperm expressed some down-regulated antioxidative genes [ 6 ]. OS is accepted as the target for clinical treatment of asthenozoospermia [ 7 ].…”
Section: Introductionmentioning
confidence: 99%